Influence of proton pump inhibitor therapy on intestinal inflammation assessed by fecal calprotectin in pediatric patients - Su Yeong Kim; Na Mi Lee; Sin Weon Yun; Soo Ahn Chae; In Seok Lim; Eung Sang Choi; Dae Yong Yi (Korean Pediatric Society, 2019)
Background An increase in the numbers of patients with gastrointestinal symptoms has recently been observed. Purpose To investigate the effects of proton pump inhibitor (PPI) therapy on intestinal inflammation in children and adolescents as confirmed by clinical manifestations and objectively assessed by fecal calprotectin (FC) level measurement. Methods Consecutive children (aged 3-18 years) who presented with gastrointestinal symptoms and were treated with or without PPI for at least 1 month were enrolled. Patients were divided into PPI and non-PPI groups. The PPI group was further subdivided by treatment duration and type of PPI used. Stool samples were collected for FC evaluation at baseline and after treatment and clinical data and FC levels were compared between the groups. Results Fifty-one patients (15 boys, 36 girls) were enrolled in the study. The PPI group included 37 patients, while the non-PPI group included 14 patients. Clinical symptoms were not significantly different. FC levels and laboratory results, including C-reactive protein levels, white blood cell count, and absolute neutrophil count, were not statistically different before versus after PPI treatment. After treatment, FC levels decreased to 8.1 mg/kg (-575.4 to 340.3 mg/kg) in the PPI group and increased to 5.6 mg/kg (-460.0 to 186.9 mg/kg) in the non-PPI group compared to those before treatment (P=0.841). The number of patients with increased FC levels was not significantly different between the 2 groups (48.6% vs. 64.3%, P=0.363), similar to that observed in patients with an FC level > 50 mg/kg (24.3% and 7.1%, P=0.250). PPI therapy type and duration did not affect the FC levels (P=0.811 and P=0.502, respectively). Conclusion Although we aimed to confirm the evidence of intestinal inflammation due to PPI use in children and adolescents through clinical symptoms and FC measurement, no significant changes were observed.